The Effect of Work Procedures, Work Motivation and Job Design on The Work Performance of Employees in The Lahat Regency Education and Culture Service - Midi Alamsah; Harun Samsuddin; Nisma Aprini (PT. Altaf Publishing Corp, 2026)
The purpose of this study is to determine and analyze the influence of work procedures, work motivation, and job design, individually and collectively, on the work performance of employees at the Lahat Regency Education and Culture Office. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial and simultaneous tests, and the coefficient of determination. The results showed that work procedures significantly influence the work performance of employees at the Lahat Regency Education and Culture Office. Work motivation significantly influences the work performance of employees at the Lahat Regency Education and Culture Office. Job design significantly influences the work performance of employees at the Lahat Regency Education and Culture Office. Work procedures, work motivation, and job design significantly influence the work performance of employees at the Lahat Regency Education and Culture Office.